VD_FINDINFO Décision / 2013 / 453 vom 12. Dezember 2012 - VD Tribunal cantonal (2012)
RISQUE DE FUITE, RISQUE DE COLLUSION, PROPORTIONNALITÉ, DÉTENTION PRÉVENTIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. b CPP (CH), 227 CPP (CH), 393 CPP (CH)